Validation and Reproducibility of a Semi-Quantitative Food Frequency Questionnaire for Use in Puerto Rican Children - Preston, Alan M; Palacios, Cristina; Rodríguez, Cindy A.; Vélez-Rodríguez, Rose M. (Puerto Rico Health Sciences Journal, 2011)
Objective: Knowledge of the diet of specific populations is of importance in the assessment of nutrient intake. Herein, we assess the reproducibility and validity of an interviewer-administered food frequency questionnaire (FFQ) in Puerto Rican children at two educational levels – elementary (ES) and high school (HS). Methods: The FFQ contained 97 items including supplements. It was administered twice (FFQ1 and FFQ2) within a 2 week interval between which three dietary food records (DFR’s) were collected. In all, 94 ES children (40 boys and 54 girls) and 89 HS children (42 boys and 47 girls) participated in this IRB-approved study. Results: Results showed correlations between FFQ1 and FFQ2 for representative macro- and micronutrients lower than reported in the literature. Correlation coefficients were higher for HS (mean R=0.43) compared to ES (mean R=0.21) and higher for girls than for boys at both school levels. Results for validation also showed lower correlations between the FFQ2 and DFR’s compared to other studies, which was higher in HS students (mean R=0.34) compared to ES students (mean R=0.10). However, these same nutrients were cross-classified into equivalent quartiles for both the FFQ and DFR with an accuracy of about 66%. Conclusion: We have designed and validated a FFQ, appropriate for use in Puerto Rican schoolchildren to estimate energy intake in younger students and energy and micronutrients in older students. The significance of this research is that there is now an updated instrument for use in dietary studies in Puerto Rican youth.